The role and importance of mentoring in physiotherapy - N. Naidoo (AOSIS, 2006)
Numerous opportunities are afforded by mentoring for career development, new knowledge, stronger theoretical and practical foundations, as well as development of leadership and problem-solving skills. In physiotherapy, mentoring as relates to practice, education and research will help to ensure the growth and future of the profession. Mentoring can be utilised in many different instances in the teaching and learning cycle of physiotherapy students and physiotherapists and can contribute towards professional growth. The benefits derived by the mentor and mentee are immense if implemented in accordance with a deep understanding of the mentoring process. The mentoring process needs to be based on intelligent reading of situations and action by the mentor and mentee for a successful relationship. Each mentoring connection is unique, therefore each person enters the relationship and process with their own values and expectations. Mentoring practices are an effective way of supporting and fostering development throughout the duration of the undergraduate physiotherapy programme, and professional and career development of physiotherapists. This article reviews the process of mentoring and its importance for implementation in physiotherapy, for undergraduate training and physiotherapy professional growth.